Age-related decline in cardiac autonomic function is not attenuated with increased physical activity - Njemanze, Hugo; Warren, Charlotte; Eggett, Christopher; MacGowan, Guy A.; Bates, Matthew G.D.; Siervo, Mario; Ivkovic, Srdjan; Trenell, Michael I.; Jakovljevic, Djordje G. (Oncotarget, 2016)
Age and physical inactivity are important risk factors for cardiovascular mortality. Heart rate response to exercise (HRRE) and heart rate recovery (HRR), measures of cardiac autonomic function, are strong predictors of mortality. The present study defined the effect of age and physical activity on HRRE and HRR. Healthy women (N=72) grouped according to age (young, 20-30 years; middle, 40-50 years; and older, 65-81 years) and daily physical activity (low active <7500, high active >12,500 steps/day) performed a maximal cardiopulmonary exercise test. The HRRE was defined as an increase in heart rate from rest to 1, 3 and 5 minutes of exercise and at 1/3 of total exercise time, and HRR as the difference in heart rate between peak exercise and 1, 2, and 3 minutes later. Age was associated with a significant decline in HRRE at 1 min and 1/3 of exercise time (r=-0.27, p=0.04, and r=-0.39, p=0.02) and HRR at 2 min and 3 min (r=-0.35, p=0.01, and r=-0.31, p=0.02). There was no significant difference in HRRE and HRR between high and low-active middle-age and older women (p>0.05). Increased level of habitual physical activity level appears to have a limited effect on age-related decline in cardiac autonomic function in women.